The plight of the whales - McCoy, J. J. (Joseph J.) 1917- (New York Macmilla/McGraw-Hill, 1989)
Discusses how whales have become endangered and the activities of conservation groups.
Includes bibliographical references (p. 139-140).
Keywords: Whales -- Juvenile literature; Wildlife conservation -- Juvenile literature; Whales; Rare animals; Wildlife conservation